Sistem Pendukung Keputusan (SPK) Pemilihan Tanaman Pangan Pada Suatu Lahan Berdasarkan Kondisi Tanah Dengan Metode Promethee - Wafina Nurul Adila; Rekyan Regasari; Heru Nurwasito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Determination of the selection of food crops in a suitable land planted based on the condition (criteria) of land is needed as a support decision-making. There are 12 criteria assessed such as temperature, rainfall, humidity, drainage, texture, soil depth, peat thickness, ph h2o, salinity, alkalinity, sulfidic depth and slope. The large number of criteria and the level of importance of different criteria make it difficult to reach a decision. Computer System using Decision (SPK) can be used as a tool to give the decision of suitable plants planted in a land easily, quickly and accurately. The Promethee method is one of the methods involved in solving Multi Criteria Decision Making (MCDM) problems. The results of ranking in this system are influenced by the choice of preference type and the determination of the threshold inserted into the Decision Support System which will be able to overcome the problem to be able to determine the suitable plant to be planted in a field. So the result of system decision giving accuracy compared with actual decision reached 89,2% by using 28 data. With high accuracy it can be said that the Promethee Method successfully meets the needs of determining the selection of plants on a land based on soil conditions.